A study on the law and enforcement regarding counterfeit handbags / Maizatul Ain Mohd and Maslina Pe Ramli - Mohd Zin, Maizatul Ain; Pe Ramli, Maslina (2008)
This research is aimed to give exposure on the issue of counterfeit handbags in Malaysia. Our objectives are to discuss the enforcement of the law regarding counterfeit handbags in Malaysia and to find ways to overcome the problem of counterfeit handbags. The law regarding counterfeit handbags is Trade Marks Act 1976. This Act provided provisions relating to the trade marks. It stated the definition of the trade marks and what amounted to registrable trade marks. We discuss the law which applicable in Malaysia and as well as in United Kingdom. Counterfeit relates to the infringement of the trade marks. The owner of the register or unregistered trade marks can sue if there is infringement of their trade marks. The procedures concerning infringement are stated in the Trade Description Act 1972. We also managed to get further information from interview session with Mr. Shaifulbahri bin Abdul Kadir, the Senior Assistant Director from Enforcement Division, Ministry of Domestic Trade and Consumer Affairs (KPDNHEP). The interview has helped us a lot in obtaining information about the enforcement regarding counterfeit handbags. In conclusion, it is hoped that our research will help in preventing counterfeit handbags from being sold in our country by stressing on the enforcement of the laws. We also seek to give recommendation based on the problems.